HOME LAB AS A STRATEGY FOR MEANINGFUL LEARNING OF MICROBIOLOGY DURING COVID-19 PANDEMIC (Proceedings of the International Conference on Education, 2021)
Meaningful learning allows students to enrich their knowledge as well as achieve personal growth. For this purpose, it is necessary to identify and address the needs and motivations of students, this can be achieved by implementing novel strategies in the teaching-learning process. Since March 2020, due to the SARS-Cov2 pandemic, face-to-face lectures were suspended in all Mexican educational institutions; this situation forced educators to make drastic changes in teaching dynamics; being the most challenging classes that required the use of laboratories. In the present study this challenge is addressed. The aim of this research was to implement at-home laboratories, during the COVID-19 pandemic, to develop essential microbiology laboratory (ML) competencies and increase student motivation. Didactic intervention was conducted during the spring semester of 2020 with biotechnology students from four ML courses. The methodology was based on using at-home laboratories for their final course project. Students worked in teams to design an experimental strategy, based on knowledge obtained through virtual laboratories, and managed to conduct these experiments with the use of materials found in each student's home; they then presented their results where competencies and learning objectives were evaluated. Descriptive statistics, including the analysis of variance and Tukey test with a confidence level of 95% to ensure significant differences, were used to analyze and measure the obtained data trends regarding ML competencies acquisition. Results showed no significant differences in the conceptual understanding of the evaluated subject after the implementation of the stated educational strategy, as part of the digitization of the course provided during pandemic confinement; these observations allow us to conclude that the implementation objective for compliance with the ML competencies was effectively achieved
Keywords: Home laboratory; Microbiology; Educational innovation; Higher Education